Late development of the categorical perception of speech sounds in pre-adolescent children - Medina, Victoria; Serniclaes, Willy (ZAS Papers in Linguistics, 2005)
While the perilinguistic child is endowed with predispositions for the categorical perception of phonetic features, their adaptation to the native language results from a long evolution from the end of the first year of age up to the adolescence. This evolution entails both a better discrimination between phonological categories, a concomitant reduction of the discrimination between within-category variants, and a higher precision of perceptual boundaries between categories. The first objective of the present study was to assess the relative importance of these modifications by comparing the perceptual performances of a group of 11 children, aged from 8 to 11 years, with those of their mothers. Our second objective was to explore the functional implications of categorical perception by comparing the performances of a group of 8 deaf children, equipped with a cochlear implant, with normal-hearing chronological age controls. The results showed that the categorical boundary was slightly more precise and that categorical perception was consistently larger in adults vs. normal-hearing children. Those among the deaf children who were able to discriminate minimal distinctions between syllables displayed categorical perception performances equivalent to those of normal-hearing controls. In conclusion, the late effect of age on the categorical perception of speech seems to be anchored in a fairly mature phonological system, as evidenced the fairly high precision of categorical boundaries in pre-adolescents. These late developments have functional implications for speech perception in difficult conditions as suggested by the relationship between categorical perception and speech intelligibility in cochlear implant children.